Visitor Relationship Marketing: A Case Study in Samosir Tourism Area - Yossie Rossanty; Muhammad Dharma Tuah Putra Nasution; Irawan Irawan (Budapest International Research and Critics University, 2021)
Visitor Relationship Marketing (VRM) is a critical idea and concept for enhancing marketing communications in order for a company to gain a competitive edge. The study shows correlations between the literature and related theories with the case study's conclusions. According to this qualitative study, COVID-19 instances influenced the VRM approach for hotels in the Samosir area. These issues are related to the Coordinating Ministry for Maritime Affairs and Investment regulations, which have established health standards for natural tourism sites in Indonesia. These measures and regulations are anticipated to increase local tourist visits to the new normal period while avoiding COVID-19 transmission. Health procedures will be implemented at nature-based tourism sites with a strong emphasis on the concepts of cleanliness, health, and safety (CHS). These principles are being implemented in order to boost visitor trust in Indonesia's post-Covid-19 tourism sector. Tourist sites, particularly those in the Samosir area, urgently need trustworthy communication actors, particularly stakeholders who might persuade and ensure that the tourist industry can be depended upon to enhance people's welfare and the national economy. Therefore, tourist sites should be adequately managed, beginning with site preparation and marketing initiatives to attract visitors. In order to promote this tourist destination, relationship marketing as an embodiment of marketing communication is required.VRM, based on the CHS principles, can help tourists establish trust and commitment, select appropriate media, minimise barriers, and actively work to ground the Toba Caldera Geopark tourism sites, which UNESCO has already designated as Global Geopark destinations. In practice, it is anticipated that the local government, as the driving force behind Geopark tourist destinations, will promote further tourism-related activities. Several of them, for instance, conducted training on CHS principles, recruited members who were relationship marketing experts, collaborated with the health department, developed trust with multiple parties to stimulate positive information, and established sponsorships to develop hospitality and tourism for Geopark tourist destinations.